JUDICAL REVIEW OF PERPETRATORS OF PREMEDITATED MURDER COMMITED ON THE BASIS OF SUPERIOR ORDERS - Situmeang, Sahat Maruli Tua; Aishah, Diani Nur (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2024)
This research delves into the judicial review of premeditated murder cases committed based on superior orders, using the case of former Chief of the Professional and Security Division of the Indonesian National Police, Inspector General Ferdy Sambo, as a focal point. The study aims to explore the legal implications, public perception, and standard procedures within the police force regarding subordinate compliance with superiors. Employing a descriptive analysis methodology, data was gathered through literature review from secondary and tertiary sources. The findings illustrate the intricate balance between accountability, legal principles, and ethical considerations in law enforcement. While acknowledging the necessity of punishment in criminal law, the research emphasizes the importance of accurately applying legal terms, especially regarding the element of premeditation, to ensure justice and uphold legal certainty. Recommendations include continuous education and training for law enforcement personnel to prevent errors and uphold ethical standards in the execution of their duties.